2014
DOI: 10.1074/jbc.m113.499129
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid Transfer Protein Is Expressed in Cerebrovascular Endothelial Cells and Involved in High Density Lipoprotein Biogenesis and Remodeling at the Blood-Brain Barrier

Abstract: Background: Liver X receptor activation promotes formation of HDL-like particles at the blood-brain barrier (BBB). Results: Cerebrovascular endothelial cells express phospholipid transfer protein (PLTP) that transfers phospholipids, remodels HDL, and supports cellular cholesterol efflux. Conclusion: PLTP is involved in HDL genesis and remodeling at the BBB. Significance: We demonstrate a direct role of PLTP in HDL metabolism at the blood-brain interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…PLTP deletion was demonstrated to increase amyloid--induced memory deficits in mice (24). Compared with the whole brain, the PLTP mRNA expression level is 6.8-fold higher in cerebral vessels (25) and PLTP may play a role in maintaining blood-brain barrier integrity, possibly through its ability to transfer vitamin E and modulate cerebrovascular oxidative stress (26). These findings collectively suggest a significant role of PLTP in both physiological and pathophysiological processes in the brain.…”
Section: Phospholipid Transfer Proteinmentioning
confidence: 98%
“…PLTP deletion was demonstrated to increase amyloid--induced memory deficits in mice (24). Compared with the whole brain, the PLTP mRNA expression level is 6.8-fold higher in cerebral vessels (25) and PLTP may play a role in maintaining blood-brain barrier integrity, possibly through its ability to transfer vitamin E and modulate cerebrovascular oxidative stress (26). These findings collectively suggest a significant role of PLTP in both physiological and pathophysiological processes in the brain.…”
Section: Phospholipid Transfer Proteinmentioning
confidence: 98%
“…Lecithin-cholesterol acyltransferase (LCAT) esterifies the incorporated cholesterol, converting the ndHDL to HDL3 (Sorci-Thomas et al, 1990). The assembly of 2 small, dense, HDL3 molecules, in the presence of phospholipid transfer protein (PLTP), induces the formation of a larger HDL2 molecule (Chirackal Manavalan et al, 2014), which can be reversed by hepatic lipase (HL) (Patsch et al, 1987). Cholesterol esters can enter the liver directly via the receptor SR-B1, or via CETP, which facilitates the 1:1 exchange of cholesterol esters from HDL2 with TAGs from very low density lipoprotein (VLDL) and LDL .…”
Section: Overview Of Cholesterol Metabolismmentioning
confidence: 99%
“…On peripheral cells or in atherosclerotic plaque, PLTP promotes the binding of HDL to cholesterol-laden macrophages and fi broblasts and assists in HDL remodeling, which improves cholesterol and phospholipid removal ( 23 ). Recent evidence demonstrated that in vitro RNA interference silencing of PLTP decreased apoA1-and HDL3-mediated cholesterol effl ux by 67 and 30%, respectively, highlighting the potential role of PLTP in RCT ( 24 ).…”
mentioning
confidence: 99%